Long-Term Effects of Law Enforcement's Post-9/11 Focus on Counterterrorism and Homeland Security - Davis, Lois M. (RAND Corporation, 2010)
In the aftermath of 9/11, many law enforcement agencies (LEAs) shifted more resources toward developing counterterrorism (CT) and homeland security (HS) capabilities. This volume examines the effects the focus on CT and HS has had on law enforcement since 9/11, including organizational changes, funding mechanisms, how the shift has affected traditional crime-prevention efforts, and an assessment of benefits, costs, and future challenges.